Callus induction and secondary metabolite profile from Elephantopus scaber L. - Junairiah Junairiah; Diah Ayu Wulandari; Edy Setiti Wida Utami; Nabilah Istighfari Zuraidassanaaz (Universitas Gadjah Mada, 2021)
Elephantopus scaber L. is a plant that has potential as traditional medicine. Callus induction and production of secondary metabolite content can be increased by culture callus using plant growth regulators. This study was purposed to investigate the effect of IBA and kinetin concentration on the induction and secondary metabolite profile of callus from E. scaber L. leaves. Leaves explant of E. scaber L. were cultured on MS medium with various combination concentrations of IBA and kinetin for 6 weeks and then callus was extracted using methanol. Secondary metabolite content from the resulting extract was analyzed using the phytochemical screening method. The result showed that the treatment of IBA 2.0 mg/L and kinetin 1.0 mg/L and treatment of IBA 2.0 mg/L and kinetin 2.5 mg/L are the fastest combination concentration to induce callus at 5.33 ± 0.577 days. Treatment of IBA 2.0 mg/L and kinetin 2.5 mg/L produced callus with the highest fresh weight and dry weight at 0.7016 ± 0.0588 grams and 0.0766 ± 0.0062 grams, respectively. The morphology of calluses grown during this study was compact with various colors appearance, such as light green, brownish green, and brown. Secondary metabolite content of methanol extract of callus E. scaber L. are flavonoids, alkaloids, terpenoids, and saponins.